PENERAPAN DALIL MUTTAFAQ DALAM PENEMUAN HUKUM ISLAM PADA HUKUM POSITIF DI INDONESIA - Miftahul Haq; Mawardi M. Saleh; Zulfahmi Bustami (Jotika Research in Business Law, 2024)
The application of Positive Law in Indonesia, especially in the practice of Religious Courts, can legal discoveries still be carried out therein. The object of this research is related to the discovery of Islamic law in realizing justice based on the belief in the Almighty God, so the author uses a qualitative normative juridical research approach. The results of the research look at positive law in Indonesia, such as Law Number 7 of 1989 as most recently amended by Law Number 50 of 2009 concerning Religious Courts, and Law Number 48 of 2009 concerning Judicial Power, confirming that: Justice is carried out "FOR JUSTICE BASED ON BELIEF IN THE ALMIGHTY GOD, which can be interpreted as a judge must have the courage to interpret, create, shape and find the law as a solution to make justice based on the Almighty Godhead a reality, fair for justice seekers, especially for religious court judges in their decisions starting by saying Bismillah Hirokhman Hirokhim which is followed by the sentence "For the sake of justice based on belief in the Almighty God; Judges at Religious Courts are not only fixated on the regulatory texts contained in positive legal rules (laws), but judges at Religious Courts must also carry out legal discovery (rechtvinding), by way of Religious Court judges using methods of interpreting laws. laws such as interpretation according to language, historical interpretation, systematic interpretation, teleological/sociological interpretation, authentic interpretation, extensive interpretation, restrictive interpretation, analogous interpretation, argumentus a contrario interpretation, taking into account the rules in forming the discovery of Islamic law or Islamic fiqh which is based on the Al-Qur'an, Sunah Rasulullah, Al-Hadith, Ijma', Qiyas, Istishlal, ihtisan, and al-urfu and as a source in the method of discovering Islamic law, the first is the Istinbath method and the second The ijtihad method is inseparable from the process of determining texts (texts) both from the Al-Quran and from the Sunnah, where in determining these texts of course one must also pay attention to the application of the muttafaq propositions in them or the agreed source of Islamic law (Muttafaq), which comes from Al Qur'an, Al Hadith, Ijma', Qiyas.